PENGARUH AGAMA DAN BUDAYA TERHADAP ETOS KERJA PEBISNIS MUSLIM SUKU BUGIS DI KABUPATEN NUNUKAN KALIMANTAN UTARA - Rahmani Timorita Yulianti; Mega Octaviani (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2014)
Business regarded as a battlefield. Plunging into the business means being ready to fight it out with the ultimate goal to reach benefit, even profit maximization. It does not mean giving tolerance to business activities deviated from ethics. Precisely ethics has a very strategic place in business. This research about Bugis moslem in Nunukan (its mean they are immigrant), that they achieved succesful in doing business as businessmen and traders. The results showed that religious and cultural background influence on the work ethic of Moslem Bugis in Nunukan North Borneo when they doing business. Their practical business related to the business activities practiced by the Prophet Muhammad, namely: honesty, discipline, and paying zakat and charity. Hard work is their effort to keep their self-esteem as identity of Bugis tribe.